A review of the numerical investigation on the scattering of Gaussian beam by complex particles - Cui, Zhiwei; Han, Yiping (Physics reports, 2014)
The study of light scattering by various particles is an active and important subject of research with myriad practical applications. During the years the scattering of plane wave by various particles has been investigated extensively. In recent years, with the development of laser sources and the tremendous expansion of their application, there has been a growing interest in the study of light scattering by various particles illuminated by a focused Gaussian beam. Since the analytical methods are only suitable for the analysis of Gaussian beam scattering by some regular particles, for complex particles with arbitrary shape and structure, one has to resort to the numerical methods. In this article, we review the recent numerical investigation on the scattering of Gaussian beam by systems of complex particles, including arbitrarily shaped conducting particles, dielectric particles, composite particles with inclusions, as well as random discrete particles and fractal soot aggregates. The essential formulations of the proposed numerical methods are outlined and the numerical results for some complex particles are also presented. This review is expected to provide useful help for the study of the interaction between the laser beams and the complex particles.